Exploring the Role of Waqf Instrument in Supporting Educational Development: A Qualitative Content Analysis - Muhammad Aiman Awalluddin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
The cost of education has increased, while the government can no longer spend money on education development. In some Muslim countries, education access and opportunities for Muslims remain prolonged. Though Islam prioritizes education advancement for its followers, education attainment among Muslims is disappointing. Scholars and researchers have proposed using the waqf concept for education development in light of potential future scenarios in the current education sector to ensure more affordable and sustainable education for Muslims. Therefore, this study explores the roles of waqf in educational development by applying qualitative content analysis using past studies as references. The study discovered that waqf plays a significant role in supporting three costs of educational development: institution establishment cost, institution operational cost, and institution admission and enrollment cost. These three costs have been proven to be solved with the waqf instrument. It can be applied to all scales of educational institutions. With that, the study contributes to minimizing the gaps in the previous literature and introduces organized roles of waqf in educational development for authorities and relevant parties’ understanding.